Characterization of SARS-CoV-2 RNA, Antibodies, and Neutralizing Capacity in Milk Produced by Women with COVID-19 - Pace, Ryan M.; Williams, Janet E.; Järvinen, Kirsi M.; Belfort, Mandy B.; Pace, Christina D. W.; Lackey, Kimberly A.; Gogel, Alexandra C.; Nguyen-Contant, Phuong; Kanagaiah, Preshetha; Fitzgerald, Theresa; Ferri, Rita; Young, Bridget; et al. (mBio, 2021)
Results from prior studies assaying human milk for the presence of SARS-CoV-2, the causative virus of COVID-19, have suggested milk may act as a potential vehicle for mother-to-child transmission. Most previous studies are limited because they followed only a few participants, were cross-sectional, and/or failed to report how milk was collected and/or analyzed. Whether mother-to-infant SARS-CoV-2 transmission can occur during breastfeeding and, if so, whether the benefits of breastfeeding outweigh this risk during maternal COVID-19 illness remain important questions. Using RT-qPCR, we did not detect SARS-CoV-2 RNA in any milk sample ( n = 37) collected from 18 women following COVID-19 diagnosis. Although we detected evidence of viral RNA on 8 out of 70 breast skin swabs, only one was considered a conclusive positive result. In contrast, 76% of the milk samples collected from women with COVID-19 contained SARS-CoV-2-specific IgA, and 80% had SARS-CoV-2-specific IgG. In addition, 62% of the milk samples were able to neutralize SARS-CoV-2 infectivity in vitro , whereas milk samples collected prior to the COVID-19 pandemic were unable to do so. Taken together, our data do not support mother-to-infant transmission of SARS-CoV-2 via milk. Importantly, milk produced by infected mothers is a beneficial source of anti-SARS-CoV-2 IgA and IgG and neutralizes SARS-CoV-2 activity. These results support recommendations to continue breastfeeding during mild-to-moderate maternal COVID-19 illness. IMPORTANCE Results from prior studies assaying human milk for the presence of SARS-CoV-2, the causative virus of COVID-19, have suggested milk may act as a potential vehicle for mother-to-child transmission. Most previous studies are limited because they followed only a few participants, were cross-sectional, and/or failed to report how milk was collected and/or analyzed. As such, considerable uncertainty remains regarding whether human milk is capable of transmitting SARS-CoV-2 from mother to child. Here, we report that repeated milk samples collected from 18 women following COVID-19 diagnosis did not contain SARS-CoV-2 RNA; however, risk of transmission via breast skin should be further evaluated. Importantly, we found that milk produced by infected mothers is a source of anti-SARS-CoV-2 IgA and IgG and neutralizes SARS-CoV-2 activity. These results support recommendations to continue breastfeeding during mild-to-moderate maternal COVID-19 illness as milk likely provides specific immunologic benefits to infants.